EFFECTS OF DROUGHT STRESS ON PHOTOSYNTHESIS AND GLUCOSE-6- PHOSPHATE DEHYDROGENASE ACTIVITY OF TWO BIOMASS ENERGY PLANTS (Jat rophacurcas L., Verniciafordii H.) - D. K. Xing; Y.Y. Wu R. Wang; W.G. Fu; Y.C. Zhou; Q. Javed (Journal of Animal and Plant Sciences, 2015)
Drought is considered the main environmental factor limiting plant growth in karst habitats. For this study, seedlings of Jatrophacurcas L. and Verniciafordii H. were submitted to a 10-day drought stress period at 5 different intensities. Photosynthesis, biomass, carbonic anhydrase (CA), and glucose-6-phosphate dehydrogenase (G6PDH) activities were determined. It was discovered that photosynthesis of the V. fordii was more sensitive to drought stress, and the water-use efficiency (WUE) of the V. fordii responded earlier in order to adapt to the induced drought stress. However, the J. curcas accumulated more biomass with better photosynthetic tolerance under drought stress. As the drought stress increased, the G6PDH activity of the V. fordii was activated at 20% or 30% PEG level, the higher G6PDH activity of the V. fordii maintained the redox equilibrium of the cells and produced NADPH for the formation of unsaturated fatty acids. As a result, the degree of unsaturation of fatty acids in the V. fordii was affected, and its cetane number and iodine value changed; thus, the fuel properties of the biodiesel were affected. Therefore, the photosynthesis and G6PDH activity of a plant should be taken into consideration when selecting appropriate biomass energy plants in karst habitats.
Keywords: biofuel; carbonic anhydrase; chlorophyll fluorescence; glucose-6-phosphate dehydrogenase; photosynthesis